2020
DOI: 10.3390/microorganisms8111821
|View full text |Cite
|
Sign up to set email alerts
|

The Acquisition of Multidrug-Resistant Bacteria in Patients Admitted to COVID-19 Intensive Care Units: A Monocentric Retrospective Case Control Study

Abstract: Whether the risk of multidrug-resistant bacteria (MDRB) acquisition in the intensive care unit (ICU) is modified by the COVID-19 crisis is unknown. In this single center case control study, we measured the rate of MDRB acquisition in patients admitted in COVID-19 ICU and compared it with patients admitted in the same ICU for subarachnoid hemorrhage (controls) matched 1:1 on length of ICU stay and mechanical ventilation. All patients were systematically and repeatedly screened for MDRB carriage. We compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 31 publications
5
22
0
6
Order By: Relevance
“…Similar to our study, no changes in detection of Enterococcus faecium infections were identified during COVID-19 restrictions. Also similar to our findings, in a Belgian study, no differences in the acquisition rate of MROs in the intensive care unit (ICU) were found before and during the COVID-19 pandemic [ 9 ]. This may be explained by the heightened prevention measures already occurring for patients within an ICU.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our study, no changes in detection of Enterococcus faecium infections were identified during COVID-19 restrictions. Also similar to our findings, in a Belgian study, no differences in the acquisition rate of MROs in the intensive care unit (ICU) were found before and during the COVID-19 pandemic [ 9 ]. This may be explained by the heightened prevention measures already occurring for patients within an ICU.…”
Section: Discussionsupporting
confidence: 91%
“…Intensive care unit studies in Italy demonstrated an increase in the rate of infections by Klebsiella carbapenemase-resistant, E. coli , and Enterococcus spp., but these studies considered both COVID-19 and no COVID-19 patients [ 24 , 25 ]. Conversely, in a Spanish study carried out in a tertiary hospital for 20 weeks before and during the COVID-19 spread, the mean incidence density of blood infections caused by MDR organisms remained stable, with a value of 0.36 ± 0.42 cases per 1000 occupied bed days in the COVID-19 period and 0.33 ± 0.28 bloodstream infections per 1000 occupied bed days in the period before the national lockdown [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reports from ICUs indicate the incidence or resistant infection acquisition at 30/1000 patients-day. The data shows that, of 72 patients, 33% acquired 31 multidrug-resistant bacteria during their stay at the ICU [ 67 ]. These high rates of acquisition of multiresistant infections may be explained with the work overload and ICU overcrowding, as well as a decreased adherence to control measures and shortages of personal protective equipment [ 25 , 27 , 28 , 51 , 68 ].…”
Section: Antibiotic Prescribing For Covid-19 and The Unnecessary Umentioning
confidence: 99%